Perkembangan Pendidikan Islam di Negara Eropa: Pendidikan Islam di Inggris - Qurrata Akyuni (2021)
Islamic education in the UK is still in an effort to pursue a more advanced direction because there are still many obstacles faced, including the lack of Islamic schools there. However, Islamic education in England with its weaknesses, but in terms of quality, is able to compete with general education. One of them Tauheedul Islam is the best school in the country with the achievements of its students. This made Islamic Education well received in the UK.